2013
DOI: 10.1021/nl401641v
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly Based Plasmonic Arrays Tuned by Atomic Layer Deposition for Extreme Visible Light Absorption

Abstract: Achieving complete absorption of visible light with a minimal amount of material is highly desirable for many applications, including solar energy conversion to fuel and electricity, where benefits in conversion efficiency and economy can be obtained. On a fundamental level, it is of great interest to explore whether the ultimate limits in light absorption per unit volume can be achieved by capitalizing on the advances in metamaterial science and nanosynthesis. Here, we combine block copolymer lithography and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
147
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 32 publications
3
147
0
Order By: Relevance
“…Again, the implementation of this concept requires an artificial composite medium made of plasmonic nanostructures. Recently, strong absorption has been experimentally observed using a gold nanoparticle array fabricated by block copolymer lithography and overcoated with a dielectric layer by atomic layer deposition [70]. As shown in Figure 4, the ultrathin composite film with a thickness of~25 nm exhibited near-perfect absorption at around 600 nm.…”
Section: Perfect Absorbermentioning
confidence: 97%
“…Again, the implementation of this concept requires an artificial composite medium made of plasmonic nanostructures. Recently, strong absorption has been experimentally observed using a gold nanoparticle array fabricated by block copolymer lithography and overcoated with a dielectric layer by atomic layer deposition [70]. As shown in Figure 4, the ultrathin composite film with a thickness of~25 nm exhibited near-perfect absorption at around 600 nm.…”
Section: Perfect Absorbermentioning
confidence: 97%
“…The optical properties of Au were modeled with surface scattering contributions taken into account. [28] Under the cylinders, PMMA, SLG, 300 nm SiO 2 and Si were stacked. The graphene was modeled as a 0.34 nm thick layer with a fixed n = 3 and an extinction coefficient varying according to k = 1.82λ where λ is the wavelength in µm.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, Sung et al (2008) showed enhanced thermal stability of Al 2 O 3 coated silver nanoparticles against high power femtosecond laser. Self-assembly based plasmonic arrays tuned by minimum thickness of ALD fabricated (<20 nm) Au dots achieved enhanced visible light absorption per volume-equivalent thickness Frontiers in Materials | Thin Solid Films in applications including conversion of solar energy into electrical power (Hägglund et al, 2013). One of the possible reason of enhancing optical transmission is conformal and precisely uniform deposition of dielectric thin films on nano-structures is its predominance over rough topographies.…”
Section: Ald-passive Layer On Metallic Nanoplasmonic Structuresmentioning
confidence: 99%